Research Challenges in IoT and its application - Kashypa, Raushan (International Journal of Computer Sciences and Engineering, 2020)
With the exponential growth of Internet of Things, it’s very important that we identify potential domains for the applications of IoT. Starting from smart cities, healthcare, smart agriculture, IoT is about to change all aspects of life. Although the current IoT enabled technologies have become advance in recent years, there are still so many problems that require attention. As IoT uses heterogeneous fields, many research problems may arise. The expansion of IoT devices in almost all areas of our lives, makes it a much focused topic for research. Thus IoT is creating way for new dimensions of research to be carried out. This paper represents recent developments in the field of IoT and talks about research challenges for the same.